Analysis of Stomach Content from Estuarine Crocodiles in Sarawak - Ruhana, Hassan; Mohd Izwan Zulaini, Abdul Gani; Mohamad Zahin Hazwan, Hamedi (UNIMAS Publisher, 2025)
The population of Estuarine crocodiles (Crocodylus porosus) in Sarawak has increased over the past three decades. This population increase is believed to be associated with the rising number of crocodile attacks on human and livestock. However, the ecological factors underlying human-crocodile conflicts (HCC) remain poorly understood. Studying the gut contents of C. porosus is essential to understand their feeding behaviour and ecological role, providing insights that could help mitigate this long-standing HCC. Therefore, this study is carried out to assess the type and the amount of non-organic and organic items found in the crocodile stomach. Five individuals of adult crocodiles were examined for stomach contents following the standard operating procedure. The analysis revealed a total of 44 pieces of non-organic items are found in the crocodile stomachs, with plastic debris is the most common, followed by metal, fabric and glass. The organic items mainly consist of skeletal remains such as skull, bones, and other remnants of prey items. The findings of this study established baseline data on stomach content of adult crocodiles in Sarawak. The heterogenous composition of ingested materials indicates a high degree of complexity in the species’ feeding behaviour. In future, more in-depth research questions should be emphasized especially pertaining to feeding activity and pattern which will be useful for sustainable management of the HCC.